Threats to a Colorado river provisioning basin under coupled future climate and societal scenarios. (11th September 2019) - Bennett, Katrina E; Tidwell, Vincent C; Llewellyn, Dagmar; Behery, Susan; Barrett, Lucas; Stansbury, Melanie; Middleton, Richard S
Abstract: Clean, reliable supplies of water are critical to the sustainability and resilience of communities, including water needed for energy and food production, industry, drinking water, and other human and ecological needs. However, water infrastructure and management in the United States are largely optimized for historic conditions—designed and operated to respond to social needs, and past mean and extreme streamflow, which may no longer apply in the future. Temperature, precipitation, ecosystem dynamics, energy and food production, and social systems are all experiencing changes, which cumulatively affect the security of water supply. Here, we examine the impact of these changes in a provisioning basin in the arid Southwest, the San Juan River, which supplies water, food, and energy to the Colorado River and the Rio Grande. Our analysis applies a multi-model framework to examine future climate and water use scenarios. Results demonstrate that the San Juan River basin could experience significant disruptions to water deliveries (−12% to −48% for the drier models) and shortages that exceed manageable thresholds (53% to 73% of water in shorted years), potentially affecting both the local basin as well as other regions that receive water and energy from the San Juan. While water stress metrics vary across the scenarios, results indicate the need for government, industry, and communities to consider options for adapting to water supply shifts. These results raise important questions regarding the resilience of water resources in basins across the West under future scenarios and implications for energy, food, and other water supply needs.